The social representations of climate change: comparison of two territories exposed to the coastal flooding risk - Constance Mambet Doue; Oscar Navarro Carrascal; Diego Restrepo; Nathalie Krien; Delphine Rommel; Colin Lemee; Marie Coquet; Denis Mercier; Ghozlane Fleury-Bahi (International Journal of Climate Change Strategies and Management, 2020)
Purpose – Based on social representation theory, this study aims to evaluate and analyze the similarities and differences between social representations of climate change held by people living in two territories, which have in common that they are exposed to coastal risks but have different socio-cultural contexts: on the one hand, Cartagena (Colombia) and on the other, Guadeloupe (French overseas department, France). Design/methodology/approach – A double approach, both quantitative and qualitative, of social representation theory was adopted. The data collection was undertaken in two phases. First, the content and organization of social representation of climate change (SRCC) was examined with a quantitative study of 946 participants for both countries, followed by a qualitative study of 63 participants for both countries also. Findings – The study finds unicity in the SRCC for the quantitative study. In contrast, the qualitative study highlights differences at the level of the institutional anchoring of the climate change phenomenon in these two different socioeconomic and political contexts. Practical implications – These results are relevant for a reflection in terms of public policies for the prevention and management of collective natural risks, as well as for the promotion of ecological behavior adapted to political and ideological contexts. Originality/value – The use of a multi-methodological approach (quantitative and qualitative) in the same research is valuable to confirm the importance of an in-depth study of the social representations of climate change because of the complexity of the phenomenon.